(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aims to identify the structural and behavioral factors that hinder increased demand for digital educational content among students of the Faculty of Economics and Political Science at Al-Jafara University. The study employs a descriptive-analytical approach, relying on a questionnaire as its primary tool. The results revealed a positive attitude among the students of the faculty towards digital educational content, as they recognize it as an investment that enhances their future job prospects. The study found that future expectations are the most influential driver shaping demand behavior, followed by awareness of the digital economy. The impact of factors related to economic and technological constraints is less pronounced. Therefore, the study recommends integrating digital economy concepts into the curricula of all disciplines to ensure that awareness transforms from mere theoretical knowledge into practical and professional practice. It also recommends directing guidance efforts at the university and encouraging faculty members to transform curricula into interactive digital content that focuses on the practical skills required in the job market to ensure sustained demand. Furthermore, it emphasizes bridging the gap between the high behavioral intentions resulting from awareness and expectations and the ability to implement them effectively by providing a stable technological environment and accessible electronic payment solutions for students